A new species of Dichaea Lindl. (Orchidaceae) from the Brazilian Amazon - Krahl, Amauri Herbert; Valsko, Jefferson José; Holanda, Ana Sofia Sousa de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
A new species of Dichaea with articulated leaves and glabrous ovary from Northern Brazil is proposed. The new species has affinity with D. ancoraelabia, but can be differentiated by vegetative and floral morphology. Dichaea diminuta is a pendent plant 2-8 cm long, whereas D. ancoraelabia is suberect with caulome up to 24 cm long. Furthermore, D. ancoraelabia has ovate floral parts, the lip has a wide base, and a minutely apiculate and subtruncate apex. In D. diminuta floral parts are lanceolate, the lip has narrow base and apiculate and concave apex.